2013
DOI: 10.4103/0971-3026.125592
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of placenta accreta

Abstract: Placenta accreta (PA) is a severe pregnancy complication which occurs when the chorionic villi (CV) invade the myometrium abnormally. Optimal management requires accurate prenatal diagnosis. Ultrasonography (USG) and magnetic resonance imaging (MRI) are the modalities for prenatal diagnosis of PA, although USG remains the primary investigation of choice. MRI is a complementary technique and reserved for further characterization when USG is inconclusive or incomplete. Breath-hold T2-weighted half-Fourier rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 13 publications
(17 reference statements)
0
24
0
1
Order By: Relevance
“…Although, there is not any statistically difference between ultrasound and magnetic resonance imaging (MRI) for diagnosing placenta percreta, high risk cases should be carefully evaluated by MRI in order to determine the degree of the invasion to adjacent organs. It was suggested in the literature to use MRI imaging when the placenta is located in the posterior wall of the uterus [ 13 , 14 ]. In the evaluation of the related complications in our series, we reported that seven cases were transferred to the ICU, 14 cases needed blood transfusions and eight underwent hysterectomy due to placenta invasion into the bladder, which was confirmed by MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Although, there is not any statistically difference between ultrasound and magnetic resonance imaging (MRI) for diagnosing placenta percreta, high risk cases should be carefully evaluated by MRI in order to determine the degree of the invasion to adjacent organs. It was suggested in the literature to use MRI imaging when the placenta is located in the posterior wall of the uterus [ 13 , 14 ]. In the evaluation of the related complications in our series, we reported that seven cases were transferred to the ICU, 14 cases needed blood transfusions and eight underwent hysterectomy due to placenta invasion into the bladder, which was confirmed by MRI.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative radiological score (CRS) was defined as the sum of 5‐point Likert scale scores (1: definitely negative, 2: probably negative, 3: neutral, 4: probably positive, 5: definitely positive) for six MR features that were previously identified as features of invasive placenta …”
Section: Methodsmentioning
confidence: 99%
“…To diagnose placenta increta in the second and third trimesters of pregnancy, magnetic resonance imaging (MRI) is used in recent years in case of dubious results of ultrasonography [22]. However, diagnostics with the help of ultrasonography (including colour Doppler) and MRI has not shown a statistically significant difference [35]. No valid criteria of MRI diagnostics are so far developed.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%